2018
DOI: 10.11124/jbisrir-2016-003123
|View full text |Cite
|
Sign up to set email alerts
|

The influence of occupation on wellbeing, as experienced by the elderly: a systematic review

Abstract: The present review shows that two factors enhance elderly people's wellbeing: first, variation and independence in undertaking activities; second, having a choice between the occupations and a structure of activities that make up daily life. The two factors are influenced by a balance between having activities alone and with others. This review is not intended to identify specific occupations that enhance elderly people's wellbeing, but rather to indicate which types of occupations enhance the wellbeing of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The independence referred to in this study is the independence of the elderly in taking care of themselves, such as in eating, dressing up, defecating, and bathing [11,[17][18]. The application of occupational therapy in the elderly is highly beneficial for elderlies with degenerative diseases since it aims to make the elderly feel happy to create a good well-being [19][20]. Occupational therapy for the elderlies is a form of treatment designed to help them lead a more productive and independent life.…”
Section: Discussionmentioning
confidence: 99%
“…The independence referred to in this study is the independence of the elderly in taking care of themselves, such as in eating, dressing up, defecating, and bathing [11,[17][18]. The application of occupational therapy in the elderly is highly beneficial for elderlies with degenerative diseases since it aims to make the elderly feel happy to create a good well-being [19][20]. Occupational therapy for the elderlies is a form of treatment designed to help them lead a more productive and independent life.…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently demonstrated that engagement in meaningful occupations positively impact on health and well-being [2,[4][5][6][7][8][9]. For example, a systematic review on the wellbeing of elderly individuals showed well-being to be dependent on and enhanced by a range of occupations that provide meaning and value to their life [10]. Similarly, Eakman et al depicted meaningful engagement in occupation to be associated with better psychological well-being and health-related quality of life [11], and a critical review provided moderate to strong evidence that occupation has an important influence on health and well-being [12].…”
Section: Introductionmentioning
confidence: 99%
“…Research has consistently demonstrated that engagement in meaningful occupations positively impact on health and well-being [2,[4][5][6][7][8][9]. For example, a systematic review on the wellbeing of elderly individuals showed wellbeing to be dependent on and enhanced by a range of occupations that provide meaning and value to their life [10]. Similarly, Eakman et al depicted meaningful engagement in occupation to be associated with better psychological well-being and health-related quality of life [11], and a critical review provided moderate to strong evidence that occupation has an important in uence on health and well-being [12].…”
Section: Introductionmentioning
confidence: 99%